Acne keloidalis nuchae: prevalence, impact, and management challenges - Ogunbiyi A (Dove Medical Press, 2016)
Adebola Ogunbiyi Dermatology Unit, Department of Medicine, College of Medicine, University of Ibadan, University College Hospital Ibadan, Oyo State, Nigeria Abstract: Acne keloidalis nuchae (AKN) also known as folliculitis keloidalis nuchae (FKN) is a chronic form of scarring folliculitis seen mostly in men of African descent. The term AKN is commonly used even though the condition is not a keloid, and the affected individuals do not have a tendency to develop keloids in other areas of the body. It is seen in post pubertal men and is rare after the age of 55 years. A few cases have been reported in females. which has been classified as a primary cicatricial alopecia since the exact cause of acne keloidalis (AK) remains unknown. However, a few inciting agents have been suggested which include androgens, inflammation, infection, trauma, genetics, and ingrowing hairs. AK shares some similar features with other forms of cicatricial alopecia and may occur together. Papules, pustules, and sometimes tumorous masses in the nuchal or occipital regions of the scalp hence the name “bumps” evolved in the environment. Despite its common occurrence, only a few seek help in hospital when lesions start to unsightly affect the individual’s quality of life. The presences of the keloidal lesions are more stressful compared to the resulting alopecia. Various attempts to reduce the bumps with corrosives, acids, and car engine oils lead to larger lesions or unsightly scars. Active lesions produce bleeding during haircuts. This is worrisome as a couple of individuals with active AK share shaving instruments at the barber shop and are at risk of acquiring or transmitting blood-borne infections. There is an urgent need to encourage safe shaving habits and treatment of lesions at onset so as to prevent unsightly lesions. Keywords: scarring alopecia, clinical features, treatment challenges